1999
DOI: 10.1128/iai.67.10.5514-5517.1999
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydospore Formation in Candida albicans Requires the Efg1p Morphogenetic Regulator

Abstract: Chlamydospore formation of the fungal pathogen Candida albicans was found to depend on the Efg1 protein, which regulates the yeast-hyphal transition. Isogenic mutants lacking EFG1or encoding T206A and T206E variants did not differentiate chlamydospores, while cek1, cph1, ortpk2 mutations had no effect. Furthermore, filamentation ofefg1 cph1 double mutants in microaerophilic conditions suggests a novel Efg1p/Cph1p-independent filamentation pathway inC. albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 22 publications
1
59
0
1
Order By: Relevance
“…However, homozygous pmt4 mutants or pmt4 pmt6 double mutants were able to form hyphae, at an accelerated rate, in alternative inducing conditions, i.e. during agar embedding or in an hypoxic atmosphere (Brown et al, 1999;Sonneborn et al, 1999). Thus, at least in the case of pmt4 mutants, structural components involved in hyphal formation appear not to be defective.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, homozygous pmt4 mutants or pmt4 pmt6 double mutants were able to form hyphae, at an accelerated rate, in alternative inducing conditions, i.e. during agar embedding or in an hypoxic atmosphere (Brown et al, 1999;Sonneborn et al, 1999). Thus, at least in the case of pmt4 mutants, structural components involved in hyphal formation appear not to be defective.…”
Section: Discussionsupporting
confidence: 57%
“…The series of homozygous and heterozygous pmt mutants was tested in standard conditions known to induce chlamydospore or hyphal formation of C. albicans. None of the pmt strains showed any effect on chlamydospore formation (Sonneborn et al, 1999). In contrast, hyphal formation of all homozygous pmt mutants, except the pmt5 mutant, was severely inhibited on Lee's medium (Fig.…”
Section: Morphogenetic Defects Of Pmt Mutantsmentioning
confidence: 99%
“…Efg1p is a transcription factor that is downstream of PKA (Lo et al ., 1997;Stoldt et al ., 1997;Sonneborn et al ., 2000;Bockmuhl et al ., 2001;Tebarth et al ., 2003). Efg1p governs multiple different morphogenetic processes including chlamydospore formation (Sonneborn et al ., 1999a), phenotypic switching (Sonneborn et al ., 1999b;Lachke et al ., 2003), and filamentous growth (Lo et al ., 1997;Stoldt et al ., 1997). A mutant lacking Efg1p has significantly reduced capacity to invade and damage endothelial cells in vitro and attenuated virulence in the mouse model of HDC (Lo et al ., 1997;Phan et al ., 2000;Sanchez et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that various signalling pathways that govern the response of C. albicans to environmental signals are also important for chlamydospore formation. Mutants lacking the morphogenetic regulator EFG1 or the MAP kinase HOG1 , which is involved in the oxidative stress response in C. albicans , are defective in chlamydospore formation (Sonneborn et al ., 1999;Alonso-Monge et al ., 2003). Additional genes that are required for efficient chlamydospore production in C. albicans were identified by screening a library of homozygous insertion mutants (Nobile et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%